Harnessing Evolution to Make Medicines (Nobel Lecture)1. Issue 41 (17th September 2019) - Winter, Gregory
Abstract : Antibody libraries and phage display have provided the key elements for the creation of a fast evolutionary system for the generation of fully human antibody medicines. Important steps leading to this development are outlined by G. Winter in his Nobel lecture.